Prophylactic endoscopic transpapillary gallbladder stenting to prevent acute cholecystitis induced after metallic stent placement for malignant biliary strictures: a retrospective study in Japan - Fumisato Kozakai; Yoshihide Kanno; Shinsuke Koshita; Takahisa Ogawa; Hiroaki Kusunose; Toshitaka Sakai; Keisuke Yonamine; Kazuaki Miyamoto; Haruka Okano; Yuto Matsuoka; Kento Hosokawa; Hidehito Sumiya; et al. (Korean Society of Gastrointestinal Endoscopy, 2024)
Background/Aims Endoscopic biliary drainage using self-expandable metallic stents (SEMSs) for malignant biliary strictures occasionally induces acute cholecystitis (AC). This study evaluated the efficacy of prophylactic gallbladder stents (GBS) during SEMS placement. Methods Among 158 patients who underwent SEMS placement for malignant biliary strictures between January 2018 and March 2023, 30 patients who attempted to undergo prophylactic GBS placement before SEMS placement were included. Results Technical success was achieved in 21 cases (70.0%). The mean diameter of the cystic duct was more significant in the successful cases (6.5 mm vs. 3.7 mm, p<0.05). Adverse events occurred for 7 patients (23.3%: acute pancreatitis in 7; non-obstructive cholangitis in 1; perforation of the cystic duct in 1 with an overlap), all of which improved with conservative treatment. No patients developed AC when the GBS placement was successful, whereas 25 of the 128 patients (19.5%) without a prophylactic GBS developed AC during the median follow-up period of 357 days (p=0.043). In the multivariable analysis, GBS placement was a significant factor in preventing AC (hazard ratio, 0.61; 95% confidence interval, 0.37-0.99; p=0.045). Conclusions GBS may contribute to the prevention of AC after SEMS placement for malignant biliary strictures.